PERLINDUNGAN HUKUM TERHADAP PEMBELI PADA PERJANJIAN PENGIKATAN JUAL BELI ATAS TANAH DAN BANGUNAN - Tajuddin Noor; Suhaila Zulkifli (Universitas Islam Sumatera Utara, 2023)
In practice, many binding sale and purchase agreements (PPJB) are carried out in buying and selling transactions of land rights as immovable objects. According to the Land Law, which underlies the sale and purchase transaction of land rights, has the basic concepts of trade and cash. However, in practice this basic and clear concept for various reasons often cannot be fulfilled. Not or have not fulfilled the requirements for the legal action of buying and selling land rights with a sale and purchase deed drawn up by the Land Deed Making Officer (PPAT) does not mean transaction cannot be made. There are other legal instruments as a legal breakthrough that can be carried out with the Deed of Sale and Purchase Agreement as a binder, as a sign of the completion of the transaction while waiting for the completeness of the requirements needed to carry out transactions with the deed of sale and purchase by the PPAT. The problem in this study is how to regulate the transactions made by prospective buyers and prospective sellers in binding sale and purchase agreements (PPJB) and how is the legal protection of the buyer in binding sale and purchase agreements (PPJB). The conclusion of this study is that the PPJB arrangements are based on articles in Civil Law, especially civil laws such as Article 1320 of the Civil Code and Article 1338 of the Civil Code and several important principles underlying the birth of the agreement to protect buyers in PPJB are: 1. The clauses contained in the PPJB notary deed. 2. There is full power of attorney (absolute) to the buyer in the PPJB deed 3. The existence of repressive protection in the event of a dispute through legal proceedings to the District Court Keywords: Legal Protection, Debtor, Sale Purchase Agreement, Land and Buildings